The Hypoxia-Inducible Factor Pathway in Adipocytes: The Role of HIF-2 in Adipose Inflammation and Hypertrophic Cardiomyopathy - Lin, Qun; Yun, Zhong (Frontiers in Endocrinology, 2015)
Under obese conditions, adipose tissue can become oxygen-deficient or hypoxic. Extensive work has been done using various diet-induced obesity models to demonstrate an important role of hypoxia-induced signaling in adipose tissue and its impact on adipose functions related to adipogenesis, insulin sensitivity, and inflammation. We have recently identified a new mechanism connecting activation of the hypoxia-sensing pathway manifested by Hypoxia-Inducible Factor (HIF) 2α to adipose tissue inflammation and hypertrophic cardiomyopathy. Interestingly, this observation is consistent with the clinical evidence showing that obesity is often associated with ventricular hypertrophy and dysfunction as well as congestive heart failure independent of other well-established risk factors including diabetes, hypertension, and coronary artery disease. This brief review will discuss the currently published genetic mouse models to determine the role of the HIF pathway in adipose tissue-associated diseases with a focus on the newly identified role of adipocyte HIF-2 in the development of hypertrophic cardiomyopathy.